RE-BRANDING BUMDES KUJATI PERDANA DESA KARANGJATI KECAMATAN PANDAAN KABUPATEN PASURUAN - Muliatie, Yurilla Endah; Indrawati, Mei; Fitryani, Fitryani; Pamungkas, Rulan; Rochmawati, Ema; Pratama, Gemilang Kurnia (STIE Pelita Nusantara, 2022)
Translator BUMDES Kujati Perdana with its business, Café Omah Pring is a business entity established by the Karangjati Village government which aims to increase creativity and productive economic business opportunities for the Village community. BUMDES which is located close to the Pandaan toll road exit makes this place has the potential to become a tourist destination or rest area. The lack of branding makes public less familiar with the existence of Café Omah Pring. The method used is introduce Café Omah Pring on social media by inviting influencers. Rebranding process is very important so that consumers know more about Cafe Omah Pring. The importance of recognition is one of the big reasons for people to know and understand a brand better. It is hoped that with the rebranding of Cafe Omah Pring it will be able to compete with other developing businesses or partners.Key words: rebranding, BUMDES, Karangjati, Pandaan, Pasuruan